Videotoracoscopic (VATS) diagnosis of neoplasmatic pleural effusion - Lis, Adam; Kobak, Grzegorz; Zamorski, Piotr; Kądziołka, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
The aim of the study was to present 23 cases of chronic pleural effusion of unknown etiology. Among numerous clinical symptoms of pleural effusion tachypnoe, tachycardia, and low breath capacity are the most often observed. An alarming increase in the number of patients suffering from the neoplasmatic disease in recent years has created a great demand for a method that would enable the diagnosis to be faster and more accurate. Rapid progress made in developing a videotoracoscopic (VATS) method has improved the effectiveness of examining pleural space. The employment of VATS method is also a satisfactory way to liberate adhesion as well as to evacuate liquid spaces and to biopsy for both diagnostic and therapeutic purposes. When a neoplasmatic process is recognised, chemical pleurodesis is used in palliative treatment of pleural effusion. A VATS method employed to treat serious diseases is safe and reliable, and, what is more, the complications are rare and easy to deal with. Death rates from the application of VATS method have not been recorded. In a period of three years 44 VATS procedures were performed. In 23 patients with symptoms of neoplasmatic disease. Those patients had previously been treated in other departments. However, numerous pleural punctures that had been applied, failed to diagnose the disease. VATS procedures were performed in an operating theatre, under general or local anaesthesia and collecting biopsy specimens from the patients’ pleural or lung surface was controlled by a video camera. After the surgery pleural space drainage was conducted until a 24-hour amount of effusion reached 50–100 ml. VATS method provided an accurate diagnosis in all the cases. As for 13 patients, a recurrence of pleural effusion was the first symptom of a malignant neoplasm in its inoperable stage. Other symptoms such as coughing and a pain in the thorax signify the great amount of effusion but they do not always occur. In most cases (82.6%) where the neoplasmatic process was recognised, effusion contained blood. Punctures that have been applied so far require 14 weeks on average to arrive at an accurate diagnosis and the amount of evacuated pleural effusion has been over 3 000 ml. With VATS method, the drainage time is approximately 4 days and the amount of pleural effusion reaches 500 ml. The complications such as a local pain and fever are not serious and last only for a short period of time. This work stresses the need to employ a videotoracoscopic method when a two-week careful examination of patients with recurring pleural effusion does not provide an infallible diagnosis.